Вплив концентрації гідроген пероксиду на травлення монокристалів Cd1-xMnxTe розчинами Н2О2–НІ–тартратна кислота - Tomashik, Z. F.; Denysyuk, R. O.; Tomashik, V. M.; Сhernyuk, O. S.; Grytsiv, V. I.; Trishchuk, L. I. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2018)
Chemical etching of the CdTe and Cd1-xMnxTe (0,3< х <0,5) solid solutions single-crystals in the iodine emerging etchants H2O2–HI–tartaric acid with the using of the various concentration of H2O2 has been investigated. The concentration dependences of the crystal etching rate have been constructed. It was shown that Mn content increasing in the composition of the solid solutions leads to the increasing of the etching rate and to the treated surface quality amelioration. The etchant compositions and the chemical-dynamic polishing schedule of the Cd1-x MnxTe solid solutions have been optimized.